Kaligrafi Islam sebagai Arena Negosiasi Politik dan Budaya: Relasi Seni, Kekuasaan, dan Identitas Islam di Indonesia - Ridwan Septiawan Nugraha; Agus Cahyana; Asep Miftahul Falah (ATRAT: Jurnal Seni Rupa, 2026)
Islamic calligraphy is not only understood as an expression of spiritual beauty but also contains social, political, and cultural dimensions. This study aims to analyze Islamic calligraphy as a site of political and cultural negotiation in Indonesia. The research employs a qualitative approach using library research and discourse analysis of relevant academic literature. The findings show that calligraphy functions as a symbol of power legitimacy in both traditional sultanates and modern institutions, a medium of cultural resistance against colonialism and radicalism, and an instrument of cultural diplomacy in shaping a moderate Islamic identity in Indonesia. These findings emphasize that calligraphy serves as a space of meaning production that reflects the dynamic relationship between art, power, and identity in Indonesian Muslim society. .